Composition, and production method of the same
Patent Information
- Application Number
- JP2023129003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-15
- Filing Date
- 2023-08-08
- Publication Date
- 2025-04-28
AI Technical Summary
Existing cellulose derivative particles used in cosmetics face challenges in achieving high dispersibility, especially in hydrophobic solvents, and their tactile sensation largely depends on particle shape and surface smoothness, necessitating improvements in particle dispersibility and texture.
Incorporating cellulose derivative particles with a surface treatment compound, such as an organic compound with a long-chain alkyl group or an inorganic powder, having an average particle diameter 1/3 or less than the cellulose derivative particles, to enhance dispersibility and tactile feel.
The composition achieves high particle dispersibility in various solvents and formulations, providing a good tactile sensation and improved texture, suitable for cosmetic compositions.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to compositions and methods for producing the same. More specifically, this disclosure relates to compositions comprising cellulose derivative particles and methods for producing the same. [Background technology]
[0002] Traditionally, cosmetics have incorporated various polymer microparticles for purposes such as improving the spreadability of cosmetics, altering texture, providing wrinkle-blurring effects, and enhancing the smoothness of foundations and other products. These microparticles have historically been made from synthetic polymers such as polyamide, polymethyl methacrylate (PMMA), polystyrene, polypropylene, and polyethylene. However, in recent years, due to the problem of marine pollution caused by microplastics, there is a growing demand for microparticles made from non-synthetic polymer materials that possess the necessary properties while being environmentally friendly, as an alternative to these synthetic polymers.
[0003] As a non-synthetic polymer, the application of fine particles made from cellulose derivatives derived from natural cellulose is being considered. For example, Patent Document 1 discloses cellulose acetate particles having an average particle diameter of 80 nm to 100 μm, a sphericity of 0.7 to 1.0, a surface smoothness of 80% to 100%, and a total acetyl substitution degree of 0.7 to 2.9.
[0004] Patent Document 2 discloses cellulose derivative particles having an alkoxy group with 2 or more carbon atoms, or an acyl group with 3 or more carbon atoms, wherein the average particle diameter is 80 nm to 100 μm, the sphericity is 70% to 100%, the surface smoothness is 80% to 100%, and the total degree of substitution is 0.7 to 3.
[0005] Patent Document 3 discloses particles containing cellulose acetate, having an average particle diameter of 80 nm to 100 μm, a sphericity of 0.7 to 1.0, a surface smoothness of 80% to 100%, a surface contact angle with water of 100° or more, and a total acetyl substitution degree of 0.7 to 2.9. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] Patent No. 6609726 [Patent Document 2] Japanese Patent Publication No. 2020-152851 [Patent Document 3] Patent No. 6694559 [Overview of the project] [Problems that the invention aims to solve]
[0007] The microparticles disclosed in Patent Documents 1-3 are said to provide a good tactile feel and light scattering (soft focus) effect suitable for cosmetic compositions. However, these effects largely depend on the particle shape, such as sphericity and surface smoothness. Furthermore, various solvents are used in cosmetic compositions depending on the application, and the formulation can be changed. High dispersibility in hydrophobic solvents and formulations is particularly required for polymer microparticles incorporated into cosmetic compositions. There is still room for improvement in the particle dispersibility of conventionally proposed microparticles.
[0008] The purpose of this disclosure is to provide a composition that has a good tactile feel regardless of particle shape and excellent particle dispersibility, as well as a method for producing the same. [Means for solving the problem]
[0009] The composition relating to this disclosure comprises cellulose derivative particles and a surface treatment compound. The average particle size of the cellulose derivative particles is 0.08 μm or more and 100 μm or less. The surface treatment compound is an organic compound and / or inorganic powder having a long-chain alkyl group. The average particle size of this inorganic powder is 1 / 3 or less of the average particle size of the cellulose derivative particles.
[0010] Preferably, the organic compound has a long-chain alkyl group with 8 to 22 carbon atoms. Preferably, the organic compound is a compound selected from cationic surfactants and metal soaps, or Nε-lauroyl-L-lysine.
[0011] Preferably, the surface treatment compound is one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride, and zinc oxide. The content of this surface treatment compound may be 3.0% by weight or more and 10.0% by weight or less.
[0012] Preferably, the cellulose derivative has an alkoxyl group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms. Preferably, the cellulose derivative is a cellulose acylate. Preferably, the cellulose derivative is a cellulose acetate. The total degree of substitution of the cellulose derivative may be 2.0 or more and 3.2 or less.
[0013] The cellulose derivative particles may have a sphericity of 0.7 to 1.0 and a surface smoothness of 80% to 100%.
[0014] The cosmetic compositions of this disclosure include any of the compositions described above.
[0015] The method for producing the composition of this disclosure comprises a mixing step of dry mixing cellulose derivative particles having an average particle diameter of 0.08 μm or more and 100 μm or less with a surface treatment compound. The surface treatment compound is an organic compound and / or inorganic powder having a long-chain alkyl group. The average particle diameter of this inorganic powder is 1 / 3 or less of the average particle diameter of the cellulose derivative particles.
[0016] This manufacturing method may further include a pulverization step of pulverizing the surface treatment compound before the mixing step.
Advantages of the Invention
[0017] According to the composition of the present disclosure, by including an organic compound having a long-chain alkyl group and / or an inorganic powder having an average particle diameter of 1 / 3 or less of the cellulose derivative particles as the surface treatment compound, a good touch feeling can be obtained, and high particle dispersibility can be achieved in various solvents and formulations used in cosmetic compositions.
Brief Description of the Drawings
[0018] [Figure 1] FIG. 1 is a SEM image of a composition according to an embodiment of the present disclosure. [Figure 2] FIG. 2 is a SEM image of a composition according to another embodiment of the present disclosure. [Figure 3] It is a drawing for explaining a method for evaluating surface smoothness (%). [Figure 4] It is a drawing for explaining a method for evaluating surface smoothness (%).
Modes for Carrying Out the Invention
[0019] Hereinafter, an example of a preferred embodiment will be specifically described. Each configuration and their combinations in each embodiment are examples, and within the scope not departing from the gist of the present disclosure, additions, omissions, substitutions, and other changes of the configuration can be made as appropriate. The present disclosure is not limited by the embodiments, but only limited by the scope of the claims. In addition, each aspect disclosed in this specification can be combined with any other feature disclosed in this specification.
[0020] In the present specification, "X to Y" indicating a range means "X or more and Y or less". Unless otherwise noted, all test temperatures are room temperature (20°C ± 5°C).
[0021] [Composition] The composition of this disclosure comprises cellulose derivative particles and a surface treatment compound. The average particle size of the cellulose derivative particles is 0.08 μm or more and 100 μm or less. The surface treatment compound is an organic compound and / or inorganic powder having a long-chain alkyl group. The average particle size of this inorganic powder is 1 / 3 or less of the average particle size of the cellulose derivative particles. In this composition, the surface treatment compound is present on the surface and / or between the particles of cellulose derivative particles having a specific average particle size.
[0022] The surface treatment compound present on the particle surface allows cellulose derivative particles to acquire surface properties suitable for solvents and formulations used in cosmetic compositions. This composition achieves high particle dispersibility in various solvents and formulations, as well as a pleasant tactile feel. Furthermore, the surface treatment compound present between the particles further enhances the tactile feel of the cellulose derivative particles.
[0023] Here, “composition” means a mixture comprising two or more compounds. In particular, a composition comprising cellulose derivative particles and a surface treatment compound is referred to as “the composition of the present disclosure.” The composition of the present disclosure is substantially a solid composition, preferably a powder. The surface treatment compound and the cellulose derivative particles may be physically attached or chemically bonded, as long as the effects of the present disclosure are obtained. Furthermore, the composition of the present disclosure may contain substances other than cellulose derivative particles and surface treatment compounds that are not specified in this specification, to the extent that the effects of the present disclosure are not hindered.
[0024] [Surface treatment compounds] The surface treatment compound in the composition of this disclosure is an organic compound and / or inorganic powder having a long-chain alkyl group. The average particle size of this inorganic powder is 1 / 3 or less of the average particle size of the cellulose derivative particles. A surface treatment compound suitable for this disclosure may be a substance that is substantially insoluble in aqueous and non-aqueous solvents. Here, "insoluble" means that the solubility in the solvent at 25°C is less than 0.1%.
[0025] The type of the organic compound having a long-chain alkyl group is not particularly limited. From the viewpoints of the solvent used in the cosmetic composition and improvement of the dispersibility in the preparation, the number of carbon atoms of the long-chain alkyl group is preferably 5 or more, more preferably 7 or more, and still more preferably 8 or more. From the viewpoint of being easily miscible with the cellulose derivative particles, the number of carbon atoms of the long-chain alkyl group is preferably 22 or less. The number of carbon atoms of the long-chain alkyl group may be 5 or more and 22 or less, may be 7 or more and 22 or less, or may be 8 or more and 22 or less. Two or more organic compounds having different alkyl groups may be used in combination.
[0026] From the viewpoint of being easily used in the production method described below, the organic compound having a long-chain alkyl group is preferably a powder. The shape of the particles forming the powder is not particularly limited and may be any of spherical, plate-like, needle-like or irregular shapes.
[0027] In the present disclosure, the organic compound having a long-chain alkyl group may be an amino acid derivative. As the amino acid derivative, Nε-lauroyl-L-lysine is preferable.
[0028] Further, in the present disclosure, the organic compound having a long-chain alkyl group may be a cationic surfactant. Examples of the cationic surfactant include quaternary ammonium salts and / or amine salts. From the viewpoints of touch feeling and improvement of particle dispersibility, the quaternary ammonium salt represented by the following general formula (1) is preferable. R 1 R 2 R 3 R 4 N + X - (1) (In the formula, X - is a halogen ion, and R 1 , R 2 , R 3 and R 4 are each independently an alkyl group having 1 to 25 carbon atoms which may have a substituent, and at least one of R 1 , R 2 , R 3 and R 4 is an alkyl group having 12 or more carbon atoms.) Specific examples of cationic surfactants represented by formula (1) include stearyltrimethylammonium chloride, distearyldimethylammonium chloride, behenyltrimethylammonium chloride, distearyldiethylammonium chloride, decyltriethylammonium chloride, decyldimethylhydroxyethylammonium chloride, coconut oil trimethylammonium chloride, coconut oil methyldihydroxyethylammonium chloride, myristyltrimethylammonium chloride, lauryltrimethylammonium chloride, distearyldimethylammonium bromide, and stearyltrimethylammonium bromide.
[0029] Furthermore, in this disclosure, the organic compound having a long-chain alkyl group may be a metal soap. A metal soap is defined as a non-alkali metal salt of a higher fatty acid. The higher fatty acid is preferably a fatty acid having 12 to 25 carbon atoms, and may be either a saturated or unsaturated fatty acid. Examples of such fatty acid soaps include zinc salts, calcium salts, magnesium salts, or aluminum salts of lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, α-linolenic acid, erucic acid, etc. Alkaline earth metal salts of fatty acids having 12 to 25 carbon atoms are preferred, zinc salts are more preferred, and zinc stearate is particularly preferred.
[0030] Figure 1 shows a scanning electron microscope image (3000x magnification) of a composition containing an organic compound having a long-chain alkyl group as a surface treatment compound. From Figure 1, it can be inferred that in this composition, the organic compound having a long-chain alkyl group is attached to the surface of the cellulose derivative particles.
[0031] In the compositions of this disclosure, the average particle diameter of the inorganic powder is 1 / 3 or less of the average particle diameter of the cellulose derivative particles. More preferably, the average particle diameter of the inorganic powder is 1 / 10 or less of the cellulose derivative particles, from the viewpoint of obtaining a good tactile feel and high particle dispersibility. The average particle diameter of the inorganic powder is the median diameter based on volume and is measured in the same manner as the average particle diameter of the cellulose derivative particles described later.
[0032] The average particle size of the inorganic powder is not particularly limited, but should be 1 / 3 or less of that of the cellulose derivative particles. However, from the viewpoint of excellent tactile properties, it is preferably 5 μm or less, and more preferably 2 μm or less. From the viewpoint of being less prone to aggregation and easily miscible with cellulose derivative particles, the average particle size of the inorganic powder is preferably 0.01 μm or more, more preferably 0.08 μm or more, and even more preferably 0.1 μm or more.
[0033] As long as the effects of this disclosure are obtained, the particle shape of the inorganic powder is not particularly limited and may be spherical, plate-shaped, needle-shaped, granular, or irregularly shaped. Preferred inorganic powders include, for example, zinc oxide, titanium oxide, magnesium oxide, boron nitride, silicon nitride, barium sulfate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, talc, mica, kaolin, sericite, mica, vermiculite, hydylite, bentonite, montmorillonite, hectorite, kaolinite, zeolite, ceramic powder, hydroxyapatite, calcium phosphate, silicic acid, aluminum silicate, magnesium silicate, aluminum magnesium silicate, calcium silicate, etc. Boron nitride and zinc oxide are preferred from the viewpoint of being easily miscible with cellulose derivative particles and providing a good texture, and zinc oxide, which has a large specific surface area, is more preferred.
[0034] Figure 2 shows a scanning electron microscope image (3000x magnification) of a composition containing inorganic powder as a surface treatment compound, the inorganic powder having an average particle size of 1 / 3 or less of that of cellulose derivative particles. In Figure 2, the white areas represent the inorganic powder. As shown in the figure, in this composition, some of the inorganic powder is present on the surface of the cellulose derivative particles, and some is present as aggregates between the particles.
[0035] The surface treatment compound included in the composition of this disclosure may be one type or two or more types. From the viewpoint of easily obtaining a good tactile feel and high particle dispersibility, a surface treatment compound that is a compound selected from cationic surfactants and metal soaps, or Nε-lauroyl-L-lysine is preferred, one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride and zinc oxide is more preferred, and one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride and particulate zinc oxide is even more preferred.
[0036] From the viewpoint of obtaining surface properties suitable for incorporation into cosmetic compositions, the content of the surface treatment compound in the composition of this disclosure is preferably 1.0% by weight or more, more preferably 3.0% by weight or more, and particularly preferably 5.0% by weight or more. From the viewpoint of not inhibiting the physical properties of cellulose derivative particles, the content of the surface treatment compound is preferably 50.0% by weight or less, more preferably 30.0% by weight or less, and particularly preferably 10.0% by weight or less. The content of the surface treatment compound may be 1.0% by weight or more and 50.0% by weight or less, 1.0% by weight or more and 30.0% by weight or less, 1.0% by weight or more and 10.0% by weight or less, 3.0% by weight or more and 50.0% by weight or less, 3.0% by weight or more and 30.0% by weight or less, 3.0% by weight or more and 10.0% by weight or less, 5.0% by weight or more and 50.0% by weight or less, 5.0% by weight or more and 30.0% by weight or less, or 5.0% by weight or more and 10.0% by weight or less. When two or more surface treatment compounds are used in combination, it is preferable that their total content satisfies the above range.
[0037] [Cellulose derivative particles] The average particle size of the cellulose derivative particles may be 0.08 μm or more and 100 μm or less, 0.1 μm or more, 1 μm or more, 2 μm or more, or 4 μm or more. It may also be 80 μm or less, 40 μm or less, 20 μm or less, or 14 μm or less. If the average particle size is 100 μm or less, the tactile feel and light scattering (soft focus) effect are further improved. Cellulose derivative particles with an average particle size of 0.08 μm or more are easy to manufacture. Regarding tactile feel, this includes not only the feel when directly touching the cellulose derivative particles, but also, for example, the feel and texture when incorporated into a cosmetic composition.
[0038] The average particle size can be measured using dynamic light scattering. Specifically, the procedure is as follows: First, cellulose derivative particles are added to pure water to a concentration of 100 ppm, and the sample is prepared by creating a pure water suspension using an ultrasonic vibrator. Then, the volume frequency particle size distribution is measured by laser diffraction (Horiba, Ltd. "Laser Diffraction / Scattering Particle Size Distribution Analyzer LA-960", ultrasonic treatment for 15 minutes, refractive index 1.500, medium (water; 1.333)). In this volume frequency particle size distribution, the particle size corresponding to 50% of the integrated scattering intensity is determined as the average particle size. That is, the average particle size (μm) in this specification is the volume-based median diameter.
[0039] The coefficient of variation of particle size for cellulose derivative particles may be between 0% and 60%, and between 2% and 50%. The coefficient of variation (%) of particle size can be calculated by the formula: standard deviation of particle size / average particle size × 100.
[0040] The sphericity of the cellulose derivative particles is preferably 0.7 to 1.0, more preferably 0.8 to 1.0, and even more preferably 0.9 to 1.0. A sphericity of 0.7 or higher provides a better tactile feel, and for example, when incorporated into a cosmetic composition, the skin feel and soft-focus effect are further improved.
[0041] Sphericity can be measured by the following method: Using images of particles observed with a scanning electron microscope (SEM), the major and minor axes of 30 randomly selected particles are measured, the minor axis / major axis ratio for each particle is determined, and the average of these minor axis / major axis ratios is taken as the sphericity. The closer the sphericity is to 1, the more perfectly spherical the particle is considered to be.
[0042] The surface smoothness of the cellulose derivative particles is preferably 80% to 100%, more preferably 85% to 100%, and even more preferably 90% to 100%. A surface smoothness of 80% or more provides a better tactile feel. The closer to 100%, the more desirable the tactile feel.
[0043] The method for measuring surface smoothness will be explained below, using Figures 3 and 4 as examples, which use sample particles with low surface smoothness. Surface smoothness can be determined by taking a scanning electron microscope image of the particle, observing the surface irregularities, and determining the area of the depressions. Specifically, a scanning electron microscope image of the particle is taken at 2500 to 5000 times magnification (see Figure 3 for an example of a particle microscope image), and the image is binarized using an image processing device Winroof (manufactured by Mitani Corporation) (see Figure 4 for the binarized image of the microscope image in Figure 3). Then, the area ratio of the depressions (shaded areas) in an arbitrary region smaller than the particle (for example, the regions shown as n1 and n2 in Figure 3) that includes the center and / or vicinity of the center of a single particle is calculated, and the surface smoothness (%) of that single particle is calculated using the following formula. The size of the region may be 5 μm square when the particle diameter is 15 μm. Surface smoothness of a single particle (%) = (1 - percentage of concave area) × 100 Area ratio of the concave area = Area of the concave area in the arbitrary region / Area of the arbitrary region In this disclosure, the surface smoothness (%) is the average value of the surface smoothness of 10 randomly selected particle samples, i.e., n1 to n10. A higher value indicates a higher surface smoothness.
[0044] The cellulose derivative forming the cellulose derivative particles of this disclosure preferably has an alkoxy group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms. The cellulose derivative may also have both an alkoxy group having 2 to 20 carbon atoms and an acyl group having 2 to 40 carbon atoms.
[0045] The number of carbon atoms in the alkoxy group of the cellulose derivative may be 3 or more, and may be 5 or more. Furthermore, the number of carbon atoms in the alkoxy group may be 18 or less, preferably 8 or less. The cellulose derivative may have two or more alkoxy groups with different numbers of carbon atoms. Also, the cellulose derivative may have both an alkoxy group with 2 to 20 carbon atoms and an alkoxy group with 1 carbon atom (methoxy group).
[0046] Examples of alkoxy groups having 2 to 20 carbon atoms include ethoxy, protoxy, butoxy, pentoxy, hexoxy, heptoxy, and octoxy groups. These alkoxy groups may have substituents as long as the effects of this disclosure are obtained.
[0047] The acyl group of the cellulose derivative may have 3 or more carbon atoms, or 4 or more carbon atoms. Furthermore, the acyl group may have 30 or fewer carbon atoms, or 20 or fewer carbon atoms. The cellulose derivative may have two or more acyl groups with different numbers of carbon atoms.
[0048] Examples of acyl groups having 2 to 40 carbon atoms include acetyl, propionyl, butyryl, pentanol(valeryl), hexanoyl, heptanol, octanoyl, nonanoyl, undecanoyl, dodecanoyl, tridecanoyl, tetradecanoyl(myristoyl), pentadecanoyl, hexadecanoyl, heptadecanoyl, and octadecanoyl(stearoyl). These acyl groups may have substituents as long as the effects of this disclosure are obtained.
[0049] From the viewpoint of obtaining a good tactile feel and particle dispersibility suitable for cosmetic compositions, cellulose derivatives having acyl groups with 2 to 40 carbon atoms (i.e., cellulose acylates) are preferred. The preferred acyl groups are one or more selected from acetyl groups, propionyl groups, and butyryl groups, and more preferably acetyl groups. The cellulose derivative of this disclosure may be cellulose acetate.
[0050] The cellulose derivative forming the cellulose derivative particles may have a total substitution degree of 0.7 to 3.2, 1.0 to 3.2, 1.4 to 3.1, or 2.0 to 3.0. This is because it facilitates the production of particles with excellent moldability and a good tactile feel.
[0051] The total degree of substitution of a cellulose derivative can be measured by the following method. First, the total degree of substitution of a cellulose derivative is the sum of the degree of substitution at positions 2, 3, and 6 of the glucose ring of the cellulose derivative. The degree of substitution at positions 2, 3, and 6 of the glucose ring of the cellulose derivative can be measured by NMR according to the method of Tezuka (Carbonydr. Res. 273, 83 (1995)). That is, the free hydroxyl group of the cellulose derivative is acylated with a carboxylic acid anhydride in pyridine. The type of carboxylic acid anhydride used here should be selected according to the purpose of analysis. For example, acetic anhydride is suitable for analyzing the degree of propionyl substitution of cellulose acetate propionate, and propionic anhydride is suitable for analyzing the degree of acetyl substitution. The solvent and acid anhydride for the acylation reaction should be appropriately selected according to the cellulose derivative to be analyzed.
[0052] The sample obtained by acylation was dissolved in deuterated chloroform. 13The 1C-NMR spectrum is measured. For example, when the substituent is an acetyl group, propionyl group, or butyryl group, the carbon signal of the acetyl group appears in the region from 169 ppm to 171 ppm in the order of positions 2, 3, and 6 from the high magnetic field side, the carbonyl carbon signal of the propionyl group appears in the region from 172 ppm to 174 ppm in the same order, and the carbon signal of the butyryl group appears in the region from 171 ppm to 173 ppm in the same order of positions 2, 3, and 6 from the high magnetic field side. To give another example, when analyzing a cellulose derivative having a propionyl group, or when analyzing the degree of propionyl substitution after treating a cellulose derivative without a propionyl group with propionic anhydride, the carbonyl carbon signal of the propionyl group appears in the region from 172 ppm to 174 ppm in the same order.
[0053] According to Tezuka's method or a similar method, the total degree of substitution of a cellulose derivative treated with carboxylic anhydride is 3.0. Therefore, by normalizing the sum of the areas of the carbonyl carbon signals of the acyl groups originally present in the cellulose derivative and the carbonyl signals of the acyl groups introduced by the carboxylic anhydride treatment to 3.0, and determining the relative abundance of acetyl groups and propionyl groups at the corresponding positions (area ratio of each signal), the degrees of acyl substitution at positions 2, 3, and 6 of the glucose ring in the original cellulose derivative can be determined. Needless to say, the substituents containing acyl groups that can be analyzed by this method are only those substituents that do not correspond to the carboxylic anhydride used in the analytical treatment.
[0054] However, if the total degree of substitution at positions 2, 3, and 6 of the glucose ring of the cellulose derivative sample is known to be 3.0, and all substituents are limited substituents such as acetyl groups and propionyl groups, the NMR spectrum can be measured by directly dissolving the sample in deuterated chloroform, excluding the acylation step. If all substituents are acetyl groups and propionyl groups, similar to the case including the acylation step, the carbon signals of the acetyl groups appear in the region from 169 ppm to 171 ppm in the order of positions 2, 3, and 6 from the highest magnetic field, and the carbon signals of the propionyl groups appear in the region from 172 ppm to 174 ppm in the same order. Therefore, the degree of substitution, such as the degree of acetyl and propionyl substitution at positions 2, 3, and 6 of the glucose ring in the cellulose derivative, can be determined from the relative abundance of acetyl groups and propionyl groups at the corresponding positions (in other words, the area ratio of each signal).
[0055] Cellulose derivative particles may or may not contain plasticizers. In this disclosure, a plasticizer refers to a compound that can increase the plasticity of a cellulose derivative. The plasticizer is not particularly limited, and examples include adipic acid-based plasticizers, citrate-based plasticizers, glutaric acid-based plasticizers, sebacic acid-based plasticizers, glycerin ester-based plasticizers, neopentyl glycol, and phosphate-based plasticizers. Cellulose derivative particles may contain two or more plasticizers. One or more selected from the group consisting of acetyltriethyl citrate, triacetin, and diacetin are preferred.
[0056] When cellulose derivative particles contain a plasticizer, the amount of plasticizer contained in the cellulose derivative particles is not particularly limited. For example, the amount may be greater than 0% by weight and 40% by weight or less, 2% by weight or more and 40% by weight or less, 10% by weight or more and 30% by weight or less, or 15% by weight or more and 20% by weight or less, relative to the weight of the cellulose derivative particles.
[0057] The plasticizer content in cellulose derivative particles is determined by dissolving the cellulose derivative particles in a solvent capable of dissolving them, and then determining the solution.1 It can be determined by measurement using H-NMR.
[0058] [Cosmetic composition] The composition disclosed herein has an excellent tactile feel and disperses well in various solvents or formulations, making it suitable for use in cosmetic compositions. Cosmetic compositions containing the composition disclosed herein can fill in skin irregularities to make them smooth and scatter light in various directions to make wrinkles and other imperfections less noticeable (soft focus effect).
[0059] Cosmetic compositions include foundations such as liquid foundations and powder foundations; concealers; sunscreens; makeup bases; lipstick and lip primers; face powders such as body powders, solid face powders and face powders; solid powder eyeshadows; wrinkle-concealing creams; and skincare lotions, and are not limited to any particular dosage form. The dosage form may be any of the following: liquids such as aqueous solutions, emulsions, and suspensions; semi-solids such as gels and creams; or solids such as powders, granules, and solids. It may also be an emulsion type such as a cream or emulsion; an oil-gel type such as a lipstick; a powder type such as a foundation; or an azole type such as a hair styling agent.
[0060] [Method for producing the composition] The method for producing the composition of this disclosure comprises a mixing step of dry mixing cellulose derivative particles having an average particle diameter of 0.08 μm or more and 100 μm or less with a surface treatment compound. The surface treatment compound is an organic compound and / or inorganic powder having a long-chain alkyl group. The average particle diameter of the inorganic powder is 1 / 3 or less of the average particle diameter of the cellulose derivative particles. According to this production method, desired surface properties can be efficiently imparted to the cellulose derivative particles without using water, organic solvents, etc. The composition obtained by this production method has a good feel and excellent dispersibility in solvents and formulations used in cosmetic compositions. This production method may optionally include a drying step of drying the mixture of cellulose derivative particles and surface treatment compound obtained in the mixing step.
[0061] In this disclosure, "dry mixing" means mixing without adding any liquid components other than those contained in the mixture subjected to the mixing process. In the manufacturing method of this disclosure, the solid content concentration of the mixture containing cellulose derivative particles and surface treatment compounds may be 90% by weight or more, 95% by weight or more, or 98% by weight or more.
[0062] As long as the effects of this disclosure are obtained, the method of dry mixing is not particularly limited, and known mixing means can be appropriately selected and used. Examples of mixing devices include ball mills, sand mills, bead mills, homogenizers, planetary mixers, and film mixers. Furthermore, the order in which the cellulose derivative particles and the surface treatment compound are mixed is not particularly limited. The cellulose derivative particles and the surface treatment compound, weighed in a predetermined ratio, may be added to the mixing device simultaneously, or a predetermined amount of the surface treatment compound may be added to the mixing device and stirred, and then the cellulose derivative particles may be added and mixed.
[0063] The mixing conditions are adjusted as appropriate according to the type and amount of each component and the type of mixer. The mixing temperature should be such that the surface treatment compound and cellulose derivative do not degrade due to heat. For example, the mixing temperature may be 50°C or lower, 40°C or lower, or 30°C or lower. Mixing at room temperature is preferred from the viewpoint of energy saving and cost reduction. The mixing time may be adjusted as appropriate depending on the manufacturing scale, mixing temperature, etc.
[0064] Specific examples of organic compounds having long-chain alkyl groups as surface treatment compounds, and inorganic powders having an average particle diameter of 1 / 3 or less of the average particle diameter of cellulose derivative particles, are as described above. A surface treatment compound consisting of one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride, and zinc oxide is preferred, and a surface treatment compound consisting of one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride, and fine-particle zinc oxide is more preferred.
[0065] In the manufacturing method of this disclosure, the amount of surface treatment compound added is not particularly limited and can be adjusted as appropriate depending on the physical properties of the cellulose derivative particles, the type of surface treatment compound, etc. From the viewpoint of improving particle dispersibility, the amount of surface treatment compound added is preferably 1.0% by weight or more, more preferably 3.0% by weight or more, and particularly preferably 5.0% by weight or more, relative to the cellulose derivative particles. From the viewpoint of suppressing aggregation, the amount of surface treatment compound added is preferably 50.0% by weight or less, more preferably 30.0% by weight or less, and particularly preferably 10.0% by weight or less. The amount of surface treatment compound added may be 1.0% by weight or more and 50.0% by weight or less, 1.0% by weight or more and 30.0% by weight or less, 1.0% by weight or more and 10.0% by weight or less, 3.0% by weight or more and 50.0% by weight or less, 3.0% by weight or more and 30.0% by weight or less, 3.0% by weight or more and 10.0% by weight or less, 5.0% by weight or more and 50.0% by weight or less, 5.0% by weight or more and 30.0% by weight or less, and 5.0% by weight or more and 10.0% by weight or less. When two or more surface treatment compounds are used in combination, it is preferable that the total amount added satisfies the above range.
[0066] If necessary, the manufacturing method of the present disclosure may further include a grinding step of grinding the surface treatment compound before the mixing step. In this grinding step, it is preferable to grind the surface treatment compound to a size smaller than the average particle size of the cellulose derivative particles. By going through this grinding step, the surface treatment compound and the cellulose derivative particles are mixed more uniformly, and the particle dispersibility of the resulting composition is improved. In addition, a decrease in tactile feel due to the inclusion of clumpy surface treatment compounds can be avoided.
[0067] The means for grinding the surface treatment compound are not particularly limited, and known grinding methods can be used. The surface treatment compound may also be ground using a mixing apparatus used in the mixing process. The grinding conditions are adjusted so that the average particle size of the resulting pulverized material is 1 / 3 or less, preferably 1 / 10 or less, of the average particle size of the added cellulose derivative particles.
[0068] If necessary, the manufacturing method of the present disclosure may include a drying step after the mixing step in which the mixture containing the surface treatment compound and cellulose derivative particles is dried. This drying method is not particularly limited, and known methods such as heat drying, reduced pressure drying, and vacuum drying may be used. From the viewpoint of high drying efficiency, the drying temperature is preferably above room temperature, may be 50°C or higher, and may be 60°C or higher. From the viewpoint of suppressing thermal degradation of the surface treatment compound, a preferred drying temperature is 120°C or lower.
[0069] [Method for producing cellulose derivative particles] The method for producing cellulose derivative particles is not particularly limited, and known methods can be used. For example, cellulose derivative particles may be obtained by a production method comprising: a first step of mixing a desired cellulose derivative with a plasticizer to obtain a cellulose derivative impregnated with a plasticizer; a second step of kneading the cellulose derivative impregnated with a plasticizer with a water-soluble polymer to obtain a dispersion in which the cellulose derivative impregnated with a plasticizer is dispersed; and a third step of removing the water-soluble polymer from the dispersion to obtain cellulose derivative particles. According to this production method, substantially spherical particles with high surface smoothness and sphericity can be obtained, further improving the tactile feel of the composition of this disclosure.
[0070] The plasticizer used in the first step is not particularly limited as long as it has a plasticizing effect in the melt extrusion process of the cellulose derivative. Specifically, the aforementioned plasticizers can be used individually or in combination of two or more as plasticizers contained in the cellulose derivative particles. One or more selected from the group consisting of acetyltriethyl citrate, triacetin, and diacetin are preferred.
[0071] The amount of plasticizer added may be greater than 0 parts by weight and 40 parts by weight or less, 2 parts by weight or more and 40 parts by weight or less, 10 parts by weight or more and 30 parts by weight or less, or 15 parts by weight or more and 20 parts by weight or less, based on 100 parts by weight of the total amount of cellulose derivative and plasticizer. By having the amount of plasticizer added within this range, particles with higher sphericity can be obtained.
[0072] The mixing of cellulose derivatives and plasticizers can be carried out dry or wet using a mixer such as a Henschel mixer. When using a mixer such as a Henschel mixer, the temperature inside the mixer may be set to a temperature at which the cellulose derivative does not melt, for example, in the range of 20°C to less than 200°C.
[0073] The mixing of cellulose derivatives and plasticizers may be carried out by melt kneading. Melt kneading can be performed by heating and mixing the cellulose derivative and plasticizer in an extruder. The kneading temperature (cylinder temperature) of the extruder may be 200°C to 230°C. Plasticization can be achieved within this temperature range to obtain a uniform mixture. The mixture can be extruded into strands and then formed into pellets by hot cutting or other methods. In this case, the die temperature may be around 220°C.
[0074] The water-soluble polymer used in the second step refers to a polymer in which, when 1 g of polymer is dissolved in 100 g of water at 25°C, the insoluble content is less than 50% by weight. Preferred water-soluble polymers include polyvinyl alcohol, polyethylene glycol, and thermoplastic starch, with polyvinyl alcohol and thermoplastic starch being more preferred. Thermoplastic starch can be obtained by known methods. Specifically, tapioca starch can be mixed with approximately 20% glycerin as a plasticizer and kneaded using a twin-screw extruder.
[0075] The amount of water-soluble polymer added may be 55 parts by weight or more and 99 parts by weight or less, based on 100 parts by weight of the total amount of the plasticizer-impregnated cellulose derivative and the water-soluble polymer. Preferably, it is 60 parts by weight or more and 90 parts by weight or less, and more preferably 65 parts by weight or more and 85 parts by weight or less.
[0076] In the second step, the mixing of the plasticizer-impregnated cellulose derivative and the water-soluble polymer can be carried out using an extruder such as a twin-screw extruder. The preferred mixing temperature (cylinder temperature) is 200°C to 280°C. Alternatively, the dispersion may be extruded in a string-like manner from a die attached to the tip of an extruder such as a twin-screw extruder, and then cut to form pellets. In this case, the die temperature may be 220°C to 300°C.
[0077] The dispersion obtained in the second step is a dispersion in which a water-soluble polymer is the dispersion medium and a cellulose derivative impregnated with a plasticizer is the dispersed phase. In other words, the water-soluble polymer is the "sea" component and the cellulose derivative impregnated with a plasticizer is the "island" component. In this dispersion, the compound constituting the island component contains the cellulose derivative and the plasticizer and is mainly spherical.
[0078] In the third step, cellulose derivative particles are obtained by removing the water-soluble polymer from the aforementioned dispersion. The method for removing the water-soluble polymer from the dispersion is not particularly limited, as long as the water-soluble polymer can be dissolved and removed from the particles. For example, a solvent such as water, methanol, ethanol, isopropanol, or a mixture thereof can be used to dissolve and remove the water-soluble polymer in the dispersion. Specifically, for example, a method can be used in which the water-soluble polymer is removed from the dispersion by mixing the dispersion and the solvent, and then separating the solvent containing the dissolved water-soluble polymer by solid-liquid separation such as filtration. When removing the water-soluble polymer by filtration after stirring and mixing the dispersion and the solvent, the stirring and filtration may be repeated multiple times in order to increase the removal efficiency.
[0079] In the third step, the plasticizer may or may not be removed from the dispersion along with the water-soluble polymer. Therefore, the resulting cellulose derivative particles may or may not contain the plasticizer.
[0080] The mixing ratio of the dispersion to the solvent may be 0.01% to 20% by weight of the dispersion, 2% to 15% by weight, or 4% to 13% by weight of the dispersion relative to the total weight of the dispersion and solvent. This range of dispersion-solvent mixing ratio allows for efficient washing and facilitates solid-liquid separation after washing.
[0081] The mixing temperature between the dispersion and the solvent is preferably 0°C to 200°C, more preferably 20°C to 110°C, and even more preferably 40°C to 80°C. This mixing temperature range allows for efficient removal of water-soluble polymers while suppressing particle deformation and aggregation due to heating. The mixing time between the dispersion and the solvent is adjusted as appropriate according to the mixing temperature and other factors.
[0082] [Method for producing cellulose derivatives] The method for producing cellulose derivatives is not particularly limited and can be produced by known manufacturing methods.
[0083] When the cellulose derivative is a cellulose ester, it can be produced by, for example, activating the raw material pulp (cellulose); acyling the activated cellulose with an esterifying agent (acyling agent); deactivating the acyling agent after the acyling reaction is complete; and maturing (saponification, hydrolysis) the resulting cellulose acylate. Alternatively, before the activation step, there may be a pretreatment step in which the raw material pulp is disintegrated and crushed, and then sprayed and mixed with acetic acid. After the maturation (saponification, hydrolysis) step, there may be a posttreatment step of precipitation separation, purification, stabilization, and drying.
[0084] When the cellulose derivative is cellulose ether, it can be produced by immersing raw material pulp (cellulose) in a mixture of a lower aliphatic alcohol such as isopropyl alcohol (IPA) or tertiary butanol (TBA), water, and an alkali metal hydroxide such as sodium hydroxide to obtain alkali cellulose, which is a precursor of cellulose ether; and further by adding an etherifying agent and slurring (precipitation). Alternatively, before the step of obtaining alkali cellulose, a pretreatment step may be included in which the raw material pulp is disintegrated and crushed, and then sprayed and mixed with acetic acid. After the slurring (precipitation) step, a posttreatment step may be included in which precipitation separation, purification, stabilization, and drying are performed. [Examples]
[0085] The effects of this disclosure will be demonstrated below by the examples provided, but this disclosure should not be interpreted restrictively based on the description of these examples.
[0086] [Example 1] A ceramic pot (capacity 300 ml) containing 400 g of ceramic balls (diameter 5 mm) was mixed with zinc stearate (manufactured by NOF Corporation) as a surface treatment compound. Subsequently, cellulose acetate particles (manufactured by Daicel Corporation, total substitution degree = 2.4, average particle size 7.1 μm) were added as cellulose derivative particles. The mixture was then rotated at 200 rpm for 1 hour using a tabletop pot mill stand (AS ONE Corporation) to obtain the composition of Example 1. The amount of zinc stearate added to the ceramic pot was adjusted so that the zinc stearate content in the composition was 5% by weight.
[0087] [Examples 2-26] The compositions of Example 2-26 were obtained in the same manner as in Example 1, except that the types and amounts of cellulose derivative particles and surface treatment compounds were as shown in Table 1-4 below. However, in Examples 4-7, 11, 12, 16, 17, 21, and 22, after adding the surface treatment compound and before adding the cellulose derivative particles, the mixture was rotated at 200 rpm for 1 to 3 hours until the average particle size was less than 1 / 3 of that of the cellulose derivative particles. In Examples 3, 10, 15, and 20, the pre-dried surface treatment compound was added to the ceramic pot. Scanning electron microscope images (3000x magnification) of the obtained compositions are shown in Figures 1 and 2. Figure 1 is an SEM image of Example 2, which used an organic compound (Nε-lauroyl-L-lysine) as the surface treatment compound, and Figure 2 is an SEM image of Example 5, which used an inorganic powder (zinc oxide) as the surface treatment compound. In Figure 2, the white fine particles are the inorganic powder.
[0088] [Comparative Examples 1-4] The compositions of Comparative Examples 1-4 were obtained in the same manner as in Example 1, except that no surface treatment compound was added and the cellulose derivative particles were as shown in Table 4 below.
[0089] [Texture (smoothness)] The tactile sensation of the examples and comparative examples was evaluated by a panel of five experts. Each composition was touched, and both smoothness and moistness were evaluated on a scale of 1 to 5. The average score of the five people was calculated and evaluated according to the following criteria. The evaluation results are shown in Table 1-4 below as tactile sensation (smoothness). Good: 5, Fairly Good: 4, Average: 3, Fairly Poor: 2, Poor: 1
[0090] [Texture (smoothness)] The tactile sensation of the examples and comparative examples was evaluated by a panel of five experts. Each composition was touched, and the smoothness was evaluated on a scale of 1 to 5. The average score of the five people was calculated and evaluated according to the following criteria. The evaluation results are shown in Table 1-4 below as tactile sensation (smoothness). Good: 5, Fairly Good: 4, Average: 3, Fairly Poor: 2, Poor: 1
[0091] [Water buoyancy] The buoyancy of the compositions in the examples and comparative examples was measured. Specifically, 1 g of the sample was accurately weighed and added to 50 mL of water, and mixed and stirred at a rotation speed of 100 rpm or higher for 30 seconds or longer. After standing for 30 seconds or longer, the particles that floated on the water were collected, dried, and their weight was measured. The weight of the particles before mixing with water was set to 100, and the ratio of the weight of the dried particles that floated on the water is shown in Table 1-4 as the buoyancy (%). A higher value indicates a higher evaluation.
[0092] [Suspension of isododecane] The degree of buoyancy in isododecane was measured for the compositions of the examples and comparative examples. Specifically, 1 g of the sample was accurately weighed and added to 50 mL of isododecane, and the mixture was stirred at a rotation speed of 100 rpm or higher for 30 seconds or longer. After standing for 30 seconds or longer, the particles that floated in the isododecane were collected, dried, and their weight was measured. The weight of the particles before mixing with isododecane was set to 100, and the ratio of the weight of the dried particles that floated in the isododecane is shown in Table 1-4 below as the degree of buoyancy in isododecane (%). A smaller value indicates a higher evaluation.
[0093] [Table 1]
[0094] [Table 2]
[0095] [Table 3]
[0096] [Table 4]
[0097] Details of the compounds shown in Table 1-4 are as follows: Cellulose acetate particles: Manufactured by Daicel Corporation, total substitution degree 2.4, average particle size 7.1 μm, sphericity 0.97, surface smoothness 100%, weight-average molecular weight 173,000 Cellulose acetate propionate particles: Manufactured by Daicel Corporation, acetyl substitution degree 0.18, propionyl substitution degree 2.40, average particle size 9.5 μm, sphericity 0.95, surface smoothness 100%, weight-average molecular weight 152,000 Cellulose acetate butyrate particles: Manufactured by Daicel Corporation, acetyl substitution degree 2.13, butyryl substitution degree 0.71, average particle size 8.2 μm, sphericity 0.96, surface smoothness 100%, weight-average molecular weight 139,000 Ethylcellulose particles: Manufactured by Daicel Corporation, total substitution degree 2.5, average particle size 7.7 μm, sphericity 0.97, surface smoothness 100%, weight-average molecular weight 182,000 Zinc stearate: Manufactured by NOF Corporation Nε-Lauroyl-L-Lysine: A brand name "Amihope LL" manufactured by Ajinomoto Co., Inc. Stearyltrimethylammonium chloride: Product name "CA-2450" manufactured by Nikko Chemical Co., Ltd. Boron nitride: Product name "SHP-3" manufactured by Mizushima Iron Alloy Co., Ltd. Zinc oxide: Product name "FINEX-50" manufactured by Sakai Chemical Co., Ltd.
[0098] [Evaluation of sebum solidification effect] Artificial sebum was added to each of the compositions of Example 12 and Comparative Example 2 in a weight ratio of 1:1 and stirred and mixed. The mixtures were left to stand at 40°C, and the state after a predetermined time was observed visually. The artificial sebum formulation consisted of 35% by weight of olive oil, 13% by weight of oleic acid, 25% by weight of jojoba oil, 15% by weight of squalene, 7% by weight of the product name "Eldew PS-203", and 5% by weight of glyceryl tri-2-ethylhexanoate.
[0099] Observation revealed that the composition of Example 12 began to solidify after 0.5 hours and was completely solidified after 1 hour. In contrast, Comparative Example 2 retained the same fluidity as at the start of the test even after 2 hours.
[0100] As shown in Table 1-4, the compositions of the examples received a higher evaluation of tactile properties compared to the compositions of the comparative examples. Furthermore, all of the compositions of the examples floated on water and settled in isododecane, indicating excellent affinity for hydrophobic solvents. In addition, compositions containing zinc oxide as a surface treatment compound showed good sebum solidification. The advantages of this disclosure are clear from these evaluation results. [Industrial applicability]
[0101] The compositions described above can be applied to the manufacture of various cosmetic compositions.
Claims
1. The present invention relates to a method for producing a cellulose derivative comprising the steps of: The cellulose derivative particles have a volume-based median diameter of 0.08 μm or more and 100 μm or less, the surface treatment compound is an organic compound and / or an inorganic powder having a long-chain alkyl group, the volume-based median diameter of the inorganic powder is ⅓ or less of the volume-based median diameter of the cellulose derivative particles; The composition, wherein the content of the surface treatment compound is 1.0% by weight or more and 50.0% by weight or less.
2. 2. The composition according to claim 1, wherein the long chain alkyl group has 8 or more and 22 or less carbon atoms.
3. 2. The composition according to claim 1, wherein the organic compound is a compound selected from cationic surfactants and metal soaps, or Nε-lauroyl-L-lysine.
4. 2. The composition according to claim 1, wherein the surface treatment compound is one or more selected from the group consisting of zinc stearate, Nε-lauroyl-L-lysine, boron nitride and zinc oxide.
5. The composition according to claim 1 , wherein the content of the surface treatment compound is 3.0% by weight or more and 10.0% by weight or less.
6. The composition according to claim 1, wherein the cellulose derivative has an alkoxyl group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms.
7. The composition according to claim 1 , wherein the cellulose derivative is a cellulose acylate.
8. The composition of claim 1 , wherein the cellulose derivative is cellulose acetate.
9. The composition according to claim 1, wherein the cellulose derivative has a total degree of substitution of 2.0 or more and 3.2 or less.
10. The composition according to claim 1 , wherein the cellulose derivative particles have a sphericity of 0.7 or more and 1.0 or less, and a surface smoothness of 80% or more and 100% or less.
11. A cosmetic composition comprising the composition according to any one of claims 1 to 10.
12. A method for producing a cellulose derivative having a volume-based median diameter of 0.08 μm or more and 100 μm or less, comprising a mixing step of dry-mixing cellulose derivative particles with a surface treatment compound, the surface treatment compound is an organic compound and / or an inorganic powder having a long-chain alkyl group, The method for producing a composition according to claim 1, wherein the volumetric median diameter of the inorganic powder is 1 / 3 or less of the volumetric median diameter of the cellulose derivative particles.
13. The method according to claim 12, further comprising a grinding step of grinding the surface treatment compound before the mixing step.